2018
DOI: 10.1177/2047487318788587
|View full text |Cite
|
Sign up to set email alerts
|

The risk association of plasma total homocysteine with acute myocardial infarction is modified by serum vitamin A

Abstract: Background Plasma total homocysteine (tHcy) has been implicated in the development of cardiovascular disease, but the mechanisms remain unclear. Vitamin A (Vit-A) is involved in homocysteine metabolism and we therefore explored the potential interaction between plasma tHcy and serum Vit-A in relation to incident acute myocardial infarction. Methods Cox proportional hazards models were used to assess the prospective relationships between tHcy and acute myocardial infarction in 2205 patients from Western Norway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In addition, one SD increase in apoA1 concentrations was associated with a 13 % risk reduction (20). In a subsequent paper from the same core population, it was shown that patients with circulating concentrations of retinol exceeding 3.20 µmol/L, one SD increase in plasma total homocysteine concentrations was associated with a 25 % increased risk of CVD in 2205 patients with suspected CAD (21). Taken together, although the findings on the relationship between serum retinol and CVD suggest that higher retinol concentrations may be beneficial compared to lower concentrations in terms of risk, elevated concentrations beyond the upper limit of the reference range, may be harmful in itself or in other ways affect CVD risk such as the reported effectmodification on other risk factors.…”
Section: Retinol and Cardiovascular Diseasementioning
confidence: 94%
See 2 more Smart Citations
“…In addition, one SD increase in apoA1 concentrations was associated with a 13 % risk reduction (20). In a subsequent paper from the same core population, it was shown that patients with circulating concentrations of retinol exceeding 3.20 µmol/L, one SD increase in plasma total homocysteine concentrations was associated with a 25 % increased risk of CVD in 2205 patients with suspected CAD (21). Taken together, although the findings on the relationship between serum retinol and CVD suggest that higher retinol concentrations may be beneficial compared to lower concentrations in terms of risk, elevated concentrations beyond the upper limit of the reference range, may be harmful in itself or in other ways affect CVD risk such as the reported effectmodification on other risk factors.…”
Section: Retinol and Cardiovascular Diseasementioning
confidence: 94%
“…In this review we show that both retinol and retinoic acid have been linked to common lifestyle diseases. Briefly, retinol has been both positively and negatively associated with CVD (13,(15)(16)(17)(18)(19), T2DM (39) and the metabolic syndrome (81), and emerging evidence suggest that retinol can modify the relationship of other common risk factors with CVD (20,21). Less work has been done on circulating concentrations of retinoic acid and disease outcomes, but observational data indicate that it is inversely related to CVD in particular (22,23), whereas the association with T2DM is less clear (39).…”
Section: Conclusion Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Serum retinol has generally been considered to be under tight homeostatic control [15], and we have previously shown that retinol in serum of patients hospitalised for suspected coronary artery disease may range beyond what has been observed in other cohorts [4][5][6][7][8][9]. Factors associated with this variation have not been elucidated to a meaningful extent in CVD patients.…”
Section: Principal Findingsmentioning
confidence: 93%
“…We have recently reported that elevated serum retinol potentiates the risk of incident acute myocardial infarctions associated with traditional risk markers in subjects hospitalised for suspected coronary artery disease, including lipids and total homocysteine [ 4 , 5 ]. The circulating retinol concentrations in these patients exceed those reported from other cohorts [ 6 9 ], and retinol concentrations above clinical reference ranges have been associated with the metabolic syndrome [ 10 ] and cardiovascular disease (CVD) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%